2017
DOI: 10.1093/cid/cix948
|View full text |Cite
|
Sign up to set email alerts
|

Management of an Outbreak of Exophiala dermatitidis Bloodstream Infections at an Outpatient Oncology Clinic

Abstract: We report the presentation and management of 17 cases of Exophiala dermatitidis and Rhodotorula mucilaginosa bloodstream infections caused by a compounded parenteral medication at an oncology clinic. Twelve patients were asymptomatic. All central venous catheters were removed and antifungal therapy, primarily voriconazole, was administered to patients. Three patients died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Exophiala is a fungi genus of the Herpotrichiellaceae family that has been involved in infections known as phaeohyphomycosis, particularly in immunocompromised hosts. Most of these infections affect the skin,44 but Exophiala can also cause systemic infections that involve the lungs or the central nervous system 44. Of particular interest, Oztas et al reported the case of a systemic infection by Exophiala dermatitidis mimicking PSC in a 24-year-old woman without immunodeficiency 45.…”
Section: Discussionmentioning
confidence: 99%
“…Exophiala is a fungi genus of the Herpotrichiellaceae family that has been involved in infections known as phaeohyphomycosis, particularly in immunocompromised hosts. Most of these infections affect the skin,44 but Exophiala can also cause systemic infections that involve the lungs or the central nervous system 44. Of particular interest, Oztas et al reported the case of a systemic infection by Exophiala dermatitidis mimicking PSC in a 24-year-old woman without immunodeficiency 45.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, it can cause mildly invasive systemic infections that are associated with significant morbidity and mortality. Typical infections are seen in immunocompromised hosts such as transplant recipients, oncology, and pediatric patients, where it manifests itself as a subcutaneous disease and rarely as deep mycoses [9,[22][23][24][25][26]. Particularly in East Asia, E. dermatitidis was detected in disseminated and neurotropic infections with high mortality [11,27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous cases concerning the clinical manifestation and diagnostic procedure have underscored the importance of considering the patient's immune status and culture test findings (10). The beta-D-glucan test has also shown some utility for detecting fungal infection (11), as 9 out of 12 cases with E. dermatitidis infection showed an increase in its level, although our case did not. Identification can also be achieved using MALDI-TOF MS, which has been shown to be a reliable way of distinguishing bacteria in community-based analyses.…”
Section: Discussionmentioning
confidence: 55%
“…Clinically, E. dermatitidis is the cause of skin chromomycosis (7). In addition, pulmonary infection with the pathogen has been reported in bronchiectasis (9) and hematological malignancy (10); outbreaks due to fungal contamination also happen (11). Fungemia caused by E. dermatitidis is known to be associated with catheter-related infection (12).…”
Section: Discussionmentioning
confidence: 99%